2022
DOI: 10.3389/fcvm.2022.946155
|View full text |Cite|
|
Sign up to set email alerts
|

Right ventricular-pulmonary arterial coupling impairment and exercise capacity in obese adults

Abstract: BackgroundObesity-related exercise intolerance may be associated with pulmonary vascular and right ventricular dysfunction. This study tested the hypothesis that decreased pulmonary vascular reserve and right ventricular (RV)-pulmonary arterial (PA) uncoupling contributes to exercise limitation in subjects with obesity.MethodsSeventeen subjects with obesity were matched to normo-weighted healthy controls. All subjects underwent; exercise echocardiography, lung diffusing capacity (DL) for nitric oxide (NO) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
0
1
0
Order By: Relevance
“…The severity of CTEPH is correlated inversely with RV-PA coupling, 26 which could be assessed by TAPSE/sPAP. 27 Furthermore, recent studies showed that RV-PA coupling is a strong prognostic indicator. 28 In our study, serum HPSE concentrations were associated with several indicators of right ventricular enlargement such as RA-t, RV-b, RV/LV, and TASPE/sPAP.…”
Section: Discussionmentioning
confidence: 99%
“…The severity of CTEPH is correlated inversely with RV-PA coupling, 26 which could be assessed by TAPSE/sPAP. 27 Furthermore, recent studies showed that RV-PA coupling is a strong prognostic indicator. 28 In our study, serum HPSE concentrations were associated with several indicators of right ventricular enlargement such as RA-t, RV-b, RV/LV, and TASPE/sPAP.…”
Section: Discussionmentioning
confidence: 99%